Implementation of the aquaponic system as a learning medium approach for junior and senior high school students at the Indonesian school of Makkah - Darmawati Darmawati; Syamsia Syamsia; Anwar Andi Rahayu; Abdurofi Ilmas; Salamat Siti Suliza; Roasanna Rosanna; Burhanuddin Burhanuddin; Akmaluddin Akmaluddin; Widodo Aris Slamet; Mustafa Mustafa; Delviana Novi (BIO Web of Conferences)
Aquaponics is an agricultural system that combines aquaculture and hydroponic cultivation systems to produce more production at a low cost, limited land resource, water and labour efficiency. Aquaponic system cultivation activities could be applied as a medium level for learning in science and social studies outside the classroom or around the school environment. The learning methods of science and social studies in the schools are mostly carried out in the classroom, while students generally have difficulty in understanding the applied materials due to less interaction with the objects and lack physical activity which effecting students’ interest to adapt the method. The community service of this activity aims to increase students' knowledge of biology and entrepreneurship subjects by using aquaponics as a fun learning medium approach. The activity was conducted at the Indonesian School of Makkah where teachers and students were joined as participants of this program. The implementation of the service activity was carried out through three stages: namely socialization, training and application. The results of the program provided incredible contribution to the enhancement of students' knowledge on biology and entrepreneurship materials at the Indonesian School of Makkah.